GEOCHEMICAL FEATURES OF CONCENTRATION OF ACTIVATION MEGAZONES OF UKRAINE - GALETSKY, L.; VOYNOVSKY, A.; NAUMENKO, U. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The regional geodynamical system, which consists of three through latitude megastructures could be distinguished on the territory of Ukraine. The majority of the ore deposits, which are characterized by complexity end connection with different-age geological formations, are located within the Ukrainian Shield. It is necessary to note, that the territories of Ukraine allocated by borders fragments of these megazones are characterized by the certain geochemical specialization. In their borders abnormal geochemical fields of many elements, first of all the rare, color and precious metals, rare elements place. It expands prospects of a presence of new deposits which are inherent for characterized rudokontrolirujushchih megazones of activization.